Stationary configurations of space tether anchored on smaller primary in three-body problem - Ferreira, A. F. S. [UNESP]; Burov, A. A.; Guerman, A. D.; Prado, A. F. B. A.; Nikonov, V. (Elsevier B.V., 2019)
Spatial dynamics of a system composed by a planet, its moon and a spacecraft tethered to the moon surface is studied in the framework of circular restricted three-body problem. The moon is assumed to be in synchronous condition (1:1 mean motion resonances) so as to keep its orientation with respect to the planet; the size of the moon is non-negligible. The tether is considered to be light and inextensible. Equilibrium configurations of the tether are identified; their stability is analyzed. The bifurcation points, where the number of equilibria changes and new branches arise, are determined. The theoretical results are applied to particular cases of the Earth-Moon, Mars-Phobos and Pluto-Charon systems.
Keywords: Tether system; Space elevator; Tether dynamics; Moon exploration; Small celestial bodies